2x-4+3x=4x-9-3x-7

Simple and best practice solution for 2x-4+3x=4x-9-3x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-4+3x=4x-9-3x-7 equation:


Simplifying
2x + -4 + 3x = 4x + -9 + -3x + -7

Reorder the terms:
-4 + 2x + 3x = 4x + -9 + -3x + -7

Combine like terms: 2x + 3x = 5x
-4 + 5x = 4x + -9 + -3x + -7

Reorder the terms:
-4 + 5x = -9 + -7 + 4x + -3x

Combine like terms: -9 + -7 = -16
-4 + 5x = -16 + 4x + -3x

Combine like terms: 4x + -3x = 1x
-4 + 5x = -16 + 1x

Solving
-4 + 5x = -16 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-4 + 5x + -1x = -16 + 1x + -1x

Combine like terms: 5x + -1x = 4x
-4 + 4x = -16 + 1x + -1x

Combine like terms: 1x + -1x = 0
-4 + 4x = -16 + 0
-4 + 4x = -16

Add '4' to each side of the equation.
-4 + 4 + 4x = -16 + 4

Combine like terms: -4 + 4 = 0
0 + 4x = -16 + 4
4x = -16 + 4

Combine like terms: -16 + 4 = -12
4x = -12

Divide each side by '4'.
x = -3

Simplifying
x = -3

See similar equations:

| 5+2y=40 | | 9x+y=7 | | 4-3y=9 | | n(n+2)=224 | | 16x^4-8x^3=1-2x | | 3n^2+7n+4=0 | | x^5+7x^4=18 | | 3x-4(-5)=9 | | 2g=g+9 | | 5(a-3)=10a-5 | | -36n^2+48n-15=0 | | =2v^2-20-78 | | 2(x-3)+9=4x-7 | | 12m-6=4(2m-1) | | 7a^2-30a+8=0 | | y=7-6 | | 5x-3=3x+13 | | 6x+6=3x-3 | | 10b-5-3b=4b-1 | | 5s^2-14s-3=0 | | x+8=4x | | (4x-6)+x=164 | | 8x+4=8x-8 | | 6(m-8)-2(3m+2)=11m-5+7 | | 2x+3y=34 | | 2(x-5)+2x=4x+20 | | x+6=6(x+2) | | -2(5w-2)=4(4-2w) | | P=x^3-20x^2+124x | | 49w^2-9=0 | | P=x^3-20x^2+24x | | Z^2-3z-40=0 |

Equations solver categories